Inclusive Economic Growth of Indonesia and Its Determinants-Recent Evidence with Provincial Data - Rini, Desi Listyo; Hamonangan Tambunan, Tulus Tahi (Asian Journal of Interdisciplinary Research, 2021)
This study evaluates Indonesia's achievement in inclusive economic growth by analyzing regional data from 34 provinces for the period 2016-2018. For that purpose, the study used three indicators of achieving inclusive economic growth, namely economic growth that reduces inequality, poverty, and unemployment (or increases employment), the Poverty-Equivalent Growth Rate (PEGR) method, and the technique of multiple linear regression analysis (i.e. the fixed effect model). This study’s results indicate that economic growth in Indonesia is not yet fully inclusive. Only a few provinces that have achieved inclusive growth. It was found that access to technology represented by the percentage of households owning a computer and access to energy represented by the percentage of households using LPG as the main fuel for cooking have positive effects on the acceleration of inclusive economic growth. in Indonesia.